Differentiation of small and medium enterprises based on headcount - Litvinenko, I.L.; Pinkovetskaya, Ju.S.; Korolkov, V.E.; Protas, V.F.; Solovyh, N.N.; Terskaya, G.A. (Revista Publicando, 2018)
In order to solve managerial tasks related to the further development of small and medium-sized enterprises (SMEs), to provide them with the necessary assistance and support, as well as to improve their operations, there must be information on how SMEs are broken down in terms of headcount. The purpose of this study was to analyze the patterns and trends characterizing the differentiation of enterprises with different headcounts, as well as employees working in these enterprises. Official statistical information was used as input data. This study was based on an analysis of how much the enterprises with a particular headcount account for in the total number of enterprises and how much the employees working in such enterprises account for in the total workforce. It was demonstrated that the high quality of input data approximation is ensured by power and exponential monotonically decreasing functions. It was discovered that the segment of enterprises with a headcount of up to 250 people is predominated by those where there are maximum 5 employees. It was also discovered that during the period from 2010 to 2013 the proportion of such enterprises increased.